Efficacy of Larimichthys crocea TASOR protein-derived peptide FAM286 against Staphylococcus aureus - Ritian Jin; Guanglei Wei; Rong Lin; Wenfeng Lin; Jude Juventus Aweya; Duo Liang; Wuyin Weng; Shen Yang (Current Research in Food Science)
Staphylococcus aureus (S. aureus) is a major foodborne pathogen, could lead cause of intestinal infections in humans. Antimicrobial peptides, as emerging antimicrobial agents, are gradually replacing traditional agents due to their highly effective and safe antimicrobial activity. In this study, a novel peptide, designated as FAM286, was identified from TASOR protein of Larimichthys crocea, which had a strong antimicrobial activity against S. aureus with a minimum bactericidal concentration (MBC) of 3.9 μg/mL and completed bacteria killing by treatment for 1.5 h. The FAM286 could increase the permeability and disrupt the integrity of cell membranes. The cell showed aggregation phenomenon and entered the apoptosis stage. In addition, the non-bactericidal concentration of FAM286 could effectively inhibit the formation of biofilm and remove mature biofilm. Molecular docking experiments further verified the binding sites of FAM286 to S. aureus biofilm proteins SarA, AgrA, and Hld. FAM286 could also bind the bacterial DNA in an embedded manner, disrupting the structure of DNA and leading to the death of bacteria. This study comprehensively evaluated the antimicrobial mechanism of the FAM286 against S. aureus and provided a theoretical basis for the prevention and control of S. aureus.